Reflecting on the past: The cultural potential of East Javanese society based on Hindu-Buddhist archaeological objects - Basundoro, Purnawan; Kurniawan, Abimardha; Indarto, Ervan Kus; Nugroho, Andri Setyo; Rinawati, Herrukmi Septa; Sasongko, Widodo Djati (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2026)
Every five years, the East Java Provincial Government endeavors to document local cultural potential into a Regional Cultural Strategy document, known as Pokok Pikiran Kebudayaan Daerah (PPKD). Nevertheless, several obstacles persist due to weak procedures and a lack of established categories. Consequently, certain cultural elements remain uninventoried because they have either become extinct or were simply overlooked. This article attempts to address these issues through a historical perspective by reviewing the cultural heritage of East Javanese society from the Hindu-Buddhist kingdom period. The methods employed include heuristic (source collection), criticism, and interpretation. Research findings indicate that while some cultural practices can still be found today, many others have vanished. The preservation of culture occurs through intergenerational transmission involving adaptation and interpretation, as well as protection via legal instruments and regulations from the central to the regional levels. The inventorying of regional culture is formally conducted through the drafting of the PPKD. However, field findings also reveal that cultural elements originating from the Hindu-Buddhist era which persist in contemporary East Javanese society have not been fully recorded in the PPKD documents. These findings underscore the importance of more meticulous cultural mapping to prevent the loss of cultural potential with deep historical roots. Furthermore, this study suggests the necessity of revitalizing various cultural elements so they may be passed down to future generations.   Setiap lima tahun sekali Pemerintah Provinsi Jawa Timur berupaya mendokumentasikan potensi kebudayaan lokal ke dalam sebuah dokumen Pokok Pikiran Kebudayaan Daerah (PPKD). Meskipun demikian, ada sejumlah kendala yang terjadi akibat lemahnya prosedur dan belum adanya kategori. Dampaknya, ada unsur-unsur kebudayaan yang tidak terinventaris akibat telah punah atau justru luput dari perhatian. Artikel ini berupaya menjawab permasalahan tersebut melalui perspektif historis dengan cara meninjau potensi kebudayaan warisan masyarakat Jawa Timur periode kerajaan Hindu-Buddha. Metode yang digunakan meliputi pengumpulan sumber, kritik, dan interpretasi. Hasil penelitian menunjukkan sebagian kebudayaan masih dapat dijumpai hingga saat ini, namun tidak sedikit pula yang telah punah. Pemertahanan kebudayaan terjadi karena pewarisan antar generasi melalui adaptasi dan interpretasi, serta perlindungan dengan instrumen hukum dan regulasi di tingkat pusat sampai daerah. Inventarisasi kebudayaan daerah dilakukan dengan penyusunan Pokok Pikiran Kebudayaan Daerah  (PPKD). Temuan lapangan juga menunjukkan bahwa anasir-anasir kebudayaan yang masih berlanjut dan diwarisi masyarakat Jawa Timur pada periode kontemporer belum seluruhnya diinventaris melalui dokumen PPKD. Temuan ini menegaskan pentingnya pemetaan kultural yang lebih cermat untuk menghindari keluputan potensi kebudayaan yang memiliki akar historis panjang. Selain itu, kajian ini menunjukkan perlunya revitalisasi sejumlah unsur kebudayaan agar dapat diwariskan bagi generasi yang akan datang.